2007
DOI: 10.1111/j.1420-9101.2007.01302.x
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of sperm morphometry in pheasants

Abstract: Post‐copulatory sexual selection is thought to be a potent evolutionary force driving the diversification of sperm shape and function across species. In birds, insemination and fertilization are separated in time and sperm storage increases the duration of sperm–female interaction and hence the opportunity for sperm competition and cryptic female choice. We performed a comparative study of 24 pheasant species (Phasianidae, Galliformes) to establish the relative importance of sperm competition and the duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 67 publications
3
48
0
Order By: Relevance
“…Increases in sperm size in species with high levels of sperm competition have been found in 8 of these studies including such diverse taxa as birds, frogs, fish, butterflies, moths and nematodes. One study has not found such a relationship in pheasants (Immler et al, 2007b), while a negative relationship has been reported in fish (Stockley et al, 1997). Interestingly, a recent study on passerine birds has revealed that while among finches (family Fringillidae) there was a positive relationship between sperm competition and sperm length, among Old World warblers (family Sylviidae) the relation was negative.…”
Section: Sperm Size and Sperm Competitionmentioning
confidence: 90%
See 1 more Smart Citation
“…Increases in sperm size in species with high levels of sperm competition have been found in 8 of these studies including such diverse taxa as birds, frogs, fish, butterflies, moths and nematodes. One study has not found such a relationship in pheasants (Immler et al, 2007b), while a negative relationship has been reported in fish (Stockley et al, 1997). Interestingly, a recent study on passerine birds has revealed that while among finches (family Fringillidae) there was a positive relationship between sperm competition and sperm length, among Old World warblers (family Sylviidae) the relation was negative.…”
Section: Sperm Size and Sperm Competitionmentioning
confidence: 90%
“…Second, in some taxa spermatozoa are stored in specialized organs in the female tract. In these cases, sperm size is often associated with the size of the sperm storage organ (Immler et al, 2007b;review in Snook, 2005). The use of an experimental approach in Drosophila has revealed that male fertilization success is determined by an interaction between sperm size and the size of the female sperm storage organ, so that when the female storage organ is long, long sperm are more successful, but there is no effect of sperm size when the female storage organ is short (Miller and Pitnick, 2002).…”
Section: Sperm Size and Sperm Competitionmentioning
confidence: 99%
“…Interestingly, morphometric sperm traits show a strong positive phenotypic correlation across species: in mammals for example, the size of the midpiece and the size of the flagellum are significantly positively correlated (r ¼ 0.44; [14,15]) as are head length and flagellum length (r ¼ 0.56; [15]). Similarly, in passerine birds and in pheasants, midpiece length and flagellum length are strongly positively correlated (passerine birds: r ¼ 0.84 [10], r ¼ 0.97 [16]; pheasants: r ¼ 0.78 [17]), suggesting that these traits show correlated evolution. However, the causes underlying this apparent correlated evolution are poorly understood.…”
Section: Introductionmentioning
confidence: 91%
“…Five sperm were measured for each male, which captures most of the intra-male variation, provides an accurate mean per male and allows detecting significant differences between males [17,24] (see the electronic supplementary material, table S3).…”
Section: (A) Datamentioning
confidence: 99%
“…Alternatively, sperm traits may evolve as an adaptation to the female reproductive tract environment [66,67], especially in species with sperm storage. In pheasants, Immler et al [68] showed that sperm velocity was negatively related to the duration of sperm storage (see also [4]), but independent of the risk of sperm competition. Given that sperm energetics probably influence sperm longevity, the effects of selection imposed by the female reproductive environment may confound a direct link between sperm competition and sperm ATP concentrations.…”
Section: (B) Sperm Competition and Sperm Atp Concentrationmentioning
confidence: 99%